2018
DOI: 10.1039/c8tc04595j
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the substitution mechanism in Eu3+:CaMoO4and Eu3+,Na+:CaMoO4phosphors

Abstract: Why is the Eu3+:CaMoO4 unit cell bigger than that of CaMoO4? Does Na+ co-doping improve the quantum yield of Eu3+:CaMoO4 phosphors?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The abnormal movement to the small angle side when y > 3% may be due to the minor non-equivalent substitution of divalent Mg 2+ or mono-valence Li + by trivalent Tm 3+ , which leads to an expansion of the lattice. [29][30][31] Figures 6a and 6b show the y dependent PLE spectra of LYMW: yTm 3+ (y = 0%, 0.1%,0.5%,1%, 2%, 3%, 4%, 6%, 8%, 10%) samples monitored at 455 nm and 475 nm, respectively. The PLE spectrum of pure LYMW: yTm 3+ (y = 0) is also presented for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The abnormal movement to the small angle side when y > 3% may be due to the minor non-equivalent substitution of divalent Mg 2+ or mono-valence Li + by trivalent Tm 3+ , which leads to an expansion of the lattice. [29][30][31] Figures 6a and 6b show the y dependent PLE spectra of LYMW: yTm 3+ (y = 0%, 0.1%,0.5%,1%, 2%, 3%, 4%, 6%, 8%, 10%) samples monitored at 455 nm and 475 nm, respectively. The PLE spectrum of pure LYMW: yTm 3+ (y = 0) is also presented for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…[83] Furthermore, in the work of Niedermeier et al [84] dealing with magnesium oxide nanoparticles with added mixtures of iron or cobalt ions, XAS was used to evaluate the coordination and symmetry around the transition-metal ions and to determine their actual oxidation state as a function of the synthesis conditions, as well as to point out a significant segregation of Fe ions into lowcoordinated sites. In a further recent work, [85] the aliovalent substitution mechanism and crystal structure of Eu 3+ :CaMoO 4 and Eu 3+ ,Na + :CaMoO 4 phosphors was addressed using complementary techniques like Raman spectroscopy and XAS. The authors evidenced, by exploiting the local atomic sensitivity of XAS, that the substitution mechanism in the two systems was different.…”
Section: Advanced Structural and Functional Characterization Of Doped Mossmentioning
confidence: 99%
“…27 No improvements in the emission of CaMoO 4 :Eu 3+ are found upon co-doping with Na + . 28 upon co-doping with Li + when compared to Na + and K + . 29 Li et al have observed Na + to be a better co-dopant for higher emission in CaMoO 4 :Tb 3+ .…”
Section: Introductionmentioning
confidence: 99%